A novel marker to determine arrhytmia risk in elite cyclists: T peak T end - Bulent Isık; Z. İsik Solak Gormus; Huseyin Aslan; Abdullah Iclı; Galip Bilen Kurklu; Ozgur Cıftcı; Turhan Togan (Türk Spor ve Egzersiz Dergisi)
In athletes, left ventricular hypertrophy is a physiological response upon routine active sports. If the hypertrophic cardiomyopathy is not diagnosed and treated, it can lead to sudden deaths in athletes. Not so much data is known whether or not it is favorable to use of Tp-e values in order to reflect the arrhythmia risks in asymptomatic elite cyclists. The aim of this study is to examine the risks of regular bike sport on potential arrhythmia in healthy active elite cyclists and veterans by using non-invasive cardiac tests. Study groups were: healthy volunteers (group 1, n=28, mean age 35.8±4.6), active cyclists (group 2, n=27, mean age 21±3.0), veteran cyclists (group 3, n=27, mean age 29.5±7.1 yr). All groups were underwent cardiological examinations, 12 derivation ECG records, transthoracic echocardiography investigations. Tp-e interval, Tp-e dispersion, corrected Tp-e interval, QT interval and Tp-e/QT ratio were calculated from ECG records. Tp-e intervals were measured with Tangent method, corrected Tp-e interval were measured with Bazett formula. Mean Tp-e interval results were as follows according to groups 1, 2, 3; 75.0±9.3, 88.1±7.0, 83.2±8.8 ms, respectively. The Tp-e interval, cTp-e interval, Tp- dispersion, QT interval, and SLI values were significantly higher in active cyclists than the veteran cyclists and the control group (p lt;0.05). Both cyclist groups had also significantly higher Tp-e interval, cTp-e interval, QT interval, Tp-e/QT, QRS time and SLI values than the control group (p lt;0.05). Furthermore, there were significant differences in Tp-e interval, cTp-e interval, Tp-e dispersion, QT interval and SLI values between the active and veteran cyclists (p lt;0.05). There were significant differences in Tp-e dispersion between active cyclists and control group or veteran cyclists (p lt; 0.01). Arrythmia related to Tp-e interval, Tp-e dispersion, corrected Tp-e interval and Tp-e/QT ratio are associated with long-term, intense bike sport training either in active cyclists or veterans. This can also be associated with left ventricular hypertrophy in active cyclists and remnant left ventricular hpertrophy in veterans.